Road Traffic Injuries among Schoolchildren from Rural and Urban Districts of South India: A Cross-Sectional Study - Y. R. Manjunatha Babu; Pallavi Sarji Uthkarsh; Gangaboraiah A (Indian Journal of Medical Specialities)
Introduction: Children are prone to road traffic injuries (RTIs) while commuting to school as pedestrians, bicyclists, motorcyclists, and occupants of vehicles. Understanding these injuries is crucial for planning injury prevention programs. There is not much data available regarding RTIs among schoolchildren during commute to schools in the urban and rural areas of South India, and the current study is an attempt to explore the burden of RTIs among schoolchildren. Objectives: The aim of the study was (1) to assess the magnitude of RTIs among rural and urban school children while commuting to schools and (2) to determine factors affecting RTIs among school children. Materials and Methods: A cross-sectional study was conducted in urban and rural districts of a state in South India, a pretested, semi-structured, self-administered questionnaire was used to collect data and analyzed using SPSS version 20. Results: Magnitude of RTIs reported was similar in urban and rural districts. Children going to Government (public schools) reported more compared to the ones going to private schools. Male children and those accompanying other schoolchildren during commute to schools reported more injuries. Conclusion: Nearly one-fourth of the schoolchildren from Bangalore urban and rural districts reported RTIs during the past 12 months.